New evaluation of species‐specific biogenic silica flux of radiolarians (Rhizaria) in the western Arctic Ocean using microfocus X‐ray computed tomography. Issue 11 (7th September 2021) - Ikenoue, Takahito; Kimoto, Katsunori; Nakamura, Yuriko; Bjørklund, Kjell R.; Kuramoto, Naoki; Ueki, Masaaki; Ota, Yuichi; Onodera, Jonaotaro; Harada, Naomi; Honda, Makio C.; Sato, Miyako; Watanabe, Eiji; et al.
Abstract: We studied time‐series fluxes of radiolarian particles collected by two sediment traps deployed at the eastern (Sta. NAP12t) and western (Sta. CAP12t) sides of the Chukchi Borderland in the Chukchi Sea from 04 October 2012 to 18 September 2013. In order to elucidate the contribution of radiolarian skeletons to the biogenic silica flux, a three‐dimensional (3D) imaging technique using microfocus X‐ray computed tomography (MXCT) was applied to radiolarian siliceous skeletons. We calculated volumes of individual radiolarian skeletons accurately using a 3D model of them, thereby estimating the mass of silica for each radiolarian species. The time‐series fluxes of radiolarian abundance were combined with the mass of radiolarian silica and were transformed to estimate fluxes of radiolarian silica. As a result, we found that the main carrier of radiolarian silica in the western Arctic Ocean was represented by only two species; that is, Amphimelissa setosa (averages: 55.2 wt% at Sta. NAP12t, 70.8 wt% at Sta. CAP12t) and Spongotrochus glacialis (averages: 36.7 wt% at Sta. NAP12t, 23.2 wt% at Sta. CAP12t). The total radiolarian silica flux was usually higher in the eastern side than that in the western side of the Chukchi Borderland. The contribution of radiolarian silica to the biogenic silica flux was less than 10 wt% in general during the sampling duration, but occasionally reached 19.6–34.8 wt% during the open water season. This suggests that not only diatoms but also radiolarians make a significant contribution in driving the silica cycle in the Arctic Ocean.